Analysis of the inhibition potential of zosuquidar derivatives on selected bacterial and fungal ABC transporters. (March 2013) - Infed, Nacera; Smits, Sander H. J.; Dittrich, Torsten; Braun, Manfred; Driessen, Arnold J. M.; Hanekop, Nils; Schmitt, Lutz
Abstract The increasing number of multidrug-resistant pathogenic microorganisms is a serious public health issue. Among the multitude of mechanisms that lead to multidrug resistance, the active extrusion of toxic compounds, mediated by MDR efflux pumps, plays an important role. In our study we analyzed the inhibitory capability of 26 synthesized zosuquidar derivatives on three ABC-type MDR efflux pumps, namely Saccharomyces cerevisiae Pdr5 as well as Lactococcus lactis LmrA and LmrCD. For Pdr5, five compounds could be identified that inhibited rhodamine 6G transport more efficiently than zosuquidar. One of these is a compound with a new catechol acetal structure that might represent a new lead compound. Furthermore, the determination of IC50 values for rhodamine 6G transport of Pdr5 with representative compounds reveals values between 0.3 and 0.9 μM. Thus the identified compounds are among the most potent inhibitors known for Pdr5. For the ABC-type efflux pumps LmrA and LmrCD from L. lactis, seven and three compounds, which inhibit the transport activity more than the lead compound zosuquidar, were found. Interestingly, transport inhibition for LmrCD was very specific, with a drastic reduction by one compound while its diastereomers showed hardly an effect. Thus, the present study reveals new potent inhibitors for the ABC-type MDR efflux pumps studied with the inhibitors of Pdr5 and LmrCD being of particular interest as these proteins are well known model systems for their homologs in pathogenic fungi and Gram-positive bacteria.